PCP: thinking beyond HIV. (5th December 2013) - Gonzalez-Estrada, Alexei; Fernandez, James
Abstract : A 40-year-old man with a previous AIDS-defining opportunistic infection and five negative HIV tests presented to our outpatient clinic. The laboratory test was relevant for less than 300 total lymphocytes on two separate occasions. He was diagnosed with idiopathic CD4 lymphocytopenia and was started on antibiotic prophylaxis for Pneumocystis carinii pneumonia and Micobacterium avium-intracellulare infection (MAI). This case report summarises the importance of further immunological characterisation in patients presenting with opportunistic infections and decreased cellular immunity.